Peer Interaction And Meaning Construction Among Esl Learners In Comprehending Texts In Second Language Context - Abu Hassan Shaari, Zaira (2008)

(untitled)
This study investigates patterns of peer interaction in the context of an English-As-A-Second Language (ESL) Secondary School Classroom, where learners work in groups and pairs on seven different reading tasks. It considers the manifestation of the learners‘ comprehension of the reading texts through the ways they constructed meaning together. The three research questions that served to guide this study are: 1) What are the patterns of interactions employed by ESL secondary school learners when they are engaged in discussions of reading texts? 2) How do the ESL secondary school learners construct meaning during their discussions of the stexts? 3) What are the conditions contributing to the emerging patterns of interactions to arrive at meaning? The study was classroom-based and exploratory in nature. Research was conducted in the natural setting of a classroom and the reading tasks were part of the regular class work. Data for the study came from a number of sources: audio recording of the learners‘ talk as they completed the reading tasks, video recording of the lessons as they progressed, observation notes, a background questionnaire survey, a series of interviews with two groups of learners and the completed tasks. The data were analysed for distinct patterns of interaction and strategy use. The approach to data analysis was qualitative in nature where categories to describe the patterns of interactions emerged from a reiterative analysis of the data. The interviews and survey data of two groups of learners were used for more detailed analysis. Each group represented a distinct pattern of peer interaction. The results from this study are discussed with relation to the sociocultural framework which views human cognitive development as originating from social interaction and language plays a mediating role in that development. Two distinct patterns of interaction were found to predominate in the data: collaborative and dominant/passive. The differences in these patterns were distinguishable in terms of the willingness of group members to work together on all aspects of the task and the willingness to contribute and engage with each other‘s contribution. The collaborative pattern is characterized by the co-construction of meaning where learners worked on understanding, involved and supported each other, ideas were deliberated in great length and developed into something more complex and mutually acceptable. As for the dominant-passive pattern, learners worked together, however, there was limited engagement with each other‘s contribution and ideas. This resulted in brief discussions of aspects of the texts, long pauses, abandonment of discussions, acceptance of shallow answers and dictation of answers by the ‗expert‘ which was rarely challenged by the others in the group. As with the collaborative group, these learners were found to employ reading comprehension strategies frequently, particularly at a more textually explicit level, such as reading aloud part/parts of the texts during the discussions. There was also evidence of the use of higher level reading comprehension strategies, however, these strategies were produced by different individuals in the group and they were often moves that were not followed up and deliberated by the others. These learners were only able to resolve 28% of the textual issues collaboratively and 56% were not resolved at all. The patterns of peer interaction remained largely stable across the different types of reading tasks, classroom instructions (group work and pair work) and across time for more proficient learners. As for the weaker learners, the patterns of peer interaction remained stable across the group tasks, however, when these learners worked in pairs with others who had similar backgrounds and proficiency levels, they demonstrated different interaction behaviours. During these activities, the learners were more active and they employed more discourse strategies, nonetheless, many episodes were not resolved collaboratively and there was still limited engagement with each other‘s contribution. Discussions were generally motivated by the ultimate aim of producing correct or acceptable answers. This was often emphasized by the teacher in her instructions and during class discussions. Because of these expectations, the more knowledgeable learners‘ were found to summarize and dictate the answers and make moves to reread and amend these answers until they felt satisfied. The efforts to produce correct or acceptable answers had also led the learners, especially those from the dominant-passive group, to stay close to the texts and to find meanings from the texts instead of exploring possible interpretations. Differences in the patterns of peer interaction and their characteristics can be explained by certain conditions that form the situational context in which the interactions take place. In this study, the conditions contributing to the emerging patterns of interaction were found to be the learners‘ proficiency in the L2 and their orientation to the activity, which were shaped by their motives, goals and perceived roles. Other conditions that helped shape the ways the learners construct meaning were the teacher and her instructional beliefs and practice and her selection of tasks. The results have important pedagogical implications, particularly for the practice of using pair and group work to promote comprehension of L2 texts in the second language reading classrooms.